Analisis Terhadap Gaya Belajar Siswa Sekolah Menengah Di Bandung - Louise M Saija (Jurnal Padegogik, 2020)
Learning style is a behavior that is intentionally done by students in the form of cognitive, affective and psychological behavior to obtain changes in learning. Information about student learning styles can help teachers determine the learning strategies to be used. This study aims to determine how the learning styles of high school students in Bandung. This is descriptive research, and the sample in this study was 275 students from several secondary schools in Bandung. The learning style measurement instrument used is the "Perceptual Learning Style Preference Questionnaire" (PLSPQ) made by Reid (1987) which states there are six learning styles (visual, tactile, auditory, group or group, kinesthetic, individual), and translated into Indonesian. The results showed that: (1) There were 20.73 percent of students who had only one dominant or "major" learning style. , (2) There are 55.27 percent of students who have more than one dominant learning style, (3) There are 24 percent of students who do not have any dominant learning style. Other results are: The majority of high school students have a kinesthetic learning style (learning through their overall body experience or involved physically in classroom experiences) and or group learning style (learning with other friends in a group) as the dominant learning style.